1983
DOI: 10.2105/ajph.73.10.1165
|View full text |Cite
|
Sign up to set email alerts
|

The association of alcohol consumption with outcome of pregnancy.

Abstract: Patterns of alcohol consumption were assessed in 12,440 pregnant women interviewed at the time of delivery. Only 92 women (0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(48 citation statements)
references
References 13 publications
5
42
0
1
Order By: Relevance
“…The lack of adverse outcomes due to consumption up to moderate levels is consistent with several previous studies of effects on either weight or HC in children ranging from birth to 24 months [9,12,24,[30][31][32][33][34][35][36][37][38][39][40][41][42]. One study that measured children at birth and then again at 6 years also found no effects associated with measures of actual alcohol consumption, although reduced HC and length were associated with a measure of indications of problem drinking [24,51].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The lack of adverse outcomes due to consumption up to moderate levels is consistent with several previous studies of effects on either weight or HC in children ranging from birth to 24 months [9,12,24,[30][31][32][33][34][35][36][37][38][39][40][41][42]. One study that measured children at birth and then again at 6 years also found no effects associated with measures of actual alcohol consumption, although reduced HC and length were associated with a measure of indications of problem drinking [24,51].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, a number of studies have found no deleterious effects on one or more of these growth parameters at birth [9,12,24,[30][31][32][33][34][35][36][37][38][39][40][41][42], at 12 months [12,41], 24 months [12], and at 4, 7, and 14 years [42]. The different findings between studies reflect a number of factors such as the duration and amount of alcohol use among different samples with findings for moderate levels of alcohol exposure being more inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent epidemiological studies have clarified that maternal lifestyles, such as smoking or drinking habits and passive smoking during pregnancy, provoke some congenital anomalies (Jones and Smith, 1973;Himmelberger et al, 1978;Ericson et al, 1979;Kuroki, 1988;Jacobson et al, 1993;Yuan et al, 1994), although there are negative reports (Borlee et al, 1978;Marbury et al, 1983;Pradat, 1992). However, to our knowledge, an association of anal atresia with smoking and/or drinking during pregnancy has not been previously reported.…”
Section: Discussionmentioning
confidence: 84%
“…187 Spontaneous Abortion. Rates of spontaneous abortion and stillbirth, often due to placental abruption, are increased among women who drink more than 2 drinks daily according to prospective cohort studies, [188][189][190][191] a retrospective cohort study, 192 and a case-control study. 193 This association has also been suggested by retrospective surveys of women from the U.S. general population 178 and obstetric populations, 192,194 although these studies do not adequately control for the increased gravidity observed among heavy-drinking women.…”
Section: Alcohol-related Consequences Unique To Womenmentioning
confidence: 99%
“…Rates of spontaneous abortion and stillbirth, often due to placental abruption, are increased among women who drink more than 2 drinks daily according to prospective cohort studies, [188][189][190][191] a retrospective cohort study, 192 and a case-control study. 193 This association has also been suggested by retrospective surveys of women from the U.S. general population 178 and obstetric populations, 192,194 although these studies do not adequately control for the increased gravidity observed among heavy-drinking women. Studies that have failed to demonstrate a relation between heavy alcohol consumption and spontaneous abortion may have been limited by retrospective designs, insufficient power, [195][196][197][198][199][200] or use of inadequate measures of alcohol consumption.…”
Section: Alcohol-related Consequences Unique To Womenmentioning
confidence: 99%